Farmacovigilância no Brasil: A relação entre polimorfismo de fármacos, efetividade e segurança dos medicamentos - Capucho, Helaine Carneiro; Mastroianni, Patricia de Carvalho [UNESP]; Cuffini, S. (My University, 2008)
In spite of the stated Brazilian policy on medicines that their quality, effectiveness and safety should be ensured at reasonable cost, hospitals in the ANVISA Surveillance Network have been receiving notifications of technical complaints, adverse reactions and suspected therapeutic ineffectiveness (STI) of medicines. The purpose of this study was to identify the medicines notified for suspicion of therapeutic ineffectiveness, at a university hospital participating in the national Surveillance Network, and to investigate the existence of polymorphs of any of the drugs involved, by examining the literature. There were 31 notifications of STI in a period of 18 months, concerning 11 different drugs, all of which were 'similar' drugs (neither original nor licensed by originator); five of these could contain polymorphs, according to the literature. However, this does not mean that the other drugs could not contain some unknown polymorphs, more studies being needed on polymorphism, especially in the cases of reported therapeutic ineffectiveness. Therefore, tests of polymorphism should be made part of the routine quality control of the raw materials during the development of medicines and in the studies of pharmaceutical equivalence to 'reference' medicines (innovative brands). The stability test should also involve a study of polymorphism, in order to confirm the solid state stability of the drug. All these measures will assure the effectiveness of medicines, since the reproducibility in the quality of pharmaceutical products could be monitored, as well as the equivalence of each production batch with the batch selected to determine the bioequivalence with the reference brand.
Pharmacovigilance in Brazil: The relationship between drug polymorphism and the effectiveness and safety of medicines
Keywords: 'Similar' drug; Generic drug; Health surveillance; Polymorphism; bioequivalence; Brazil; drug efficacy; drug manufacture; drug safety; drug stability; drug surveillance program; licence; policy; quality control; reproducibility; solid state; university hospital